2018
DOI: 10.5937/aaser1846125g
|View full text |Cite
|
Sign up to set email alerts
|

Global organic food market

Abstract: Organic agricultural production enables the production of controlled, certified, safe, and high-quality food, and at the same time it provides high economic and ecological profit and preserves a healthy environment. Consumer interests in products of organic origin have been steadily growing for twenty years. The aim of this paper is to give an overview of the situation in the global organic food market, as well as to point out the most important motives for consumers to decide on the consumption of organically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 18 publications
0
17
0
Order By: Relevance
“…For example, consumers are willing to pay 5-50% higher price because they see that cost as an investment in their health (Chandrashekar, 2014). One research conducted in Serbia showed that a surprisingly significant part of consumers are willing to pay a higher price for organic products compared to conventional ones (Golijan and Dimitrijević, 2018).…”
Section: Pricementioning
confidence: 99%
“…For example, consumers are willing to pay 5-50% higher price because they see that cost as an investment in their health (Chandrashekar, 2014). One research conducted in Serbia showed that a surprisingly significant part of consumers are willing to pay a higher price for organic products compared to conventional ones (Golijan and Dimitrijević, 2018).…”
Section: Pricementioning
confidence: 99%
“…In response to consumer demand, organic food products are quickly growing (Peng, 2019). All countries around the world report a trend of continual growth in the organic food and beverage market (Golijan & Dimitrijević, 2018). The demand for organic products has been reported to be increasing in both local and international markets (Declaro-Ruedas, 2019), and is expected to continue growing, especially in developed countries, while the supply of organic products is limited and still cannot produce enough organic products to meet the market demand.…”
Section: Introductionmentioning
confidence: 99%
“…Consumers have more information about the food market and are becoming more concerned about living healthily (Grubor & Djokić, 2016). Therefore, producers should be more focused on consumer perceptions towards organic products in order to meet consumers' needs (Schleenbecker & Hamm, 2013;Xie et al, 2015;Golijan & Dimitrijević, 2018). The Prospects of development of organic food production in Serbia can estimate on the base of state support to this form of production and requirements of customers on market for organic products.…”
Section: Introductionmentioning
confidence: 99%